Locus of Control in College Students with and Without Visual Impairments, and the Visual Characteristics that Affect It. (January 2021) - Abbasi Jondani, Javad
Introduction: According to previous research, locus of control (LOC) has a crucial role in an individual's psychological well-being. The purpose of this study was 3-fold: (1) comparing LOC of college students with and without visual impairments while controlling for gender, educational level, and age; (2) investigating the relationship between LOC and visual characteristics in college students with visual impairments; and (3) predicting LOC of these students using their visual characteristics. Methods: The design of this study was causal-comparative. The statistical population included a sample of college students with and without visual impairments who were enrolled at the University of Isfahan, Iran. Fifteen of the 20 college students with visual impairments were selected through convenience sampling and amongst sighted students, 15 individuals were selected in a way that they were matched with college students with visual impairment regarding gender, educational level, and age. The Rotter Locus of Control Scale was used to measure LOC. Also, visual impairment characteristics and demographic data were collected. The results were analyzed by t -test and stepwise regression analysis. Results: Results indicated no significant difference between LOC of college students with and without visual impairments ( p > .05), and both groups tended to have internal LOC on average. The results indicated that adjustment to visual impairment and the recent status of visual impairment might predict the LOC of a college student who is visually impaired and explained 59.2% of its variance with this sample ( p < .005). Discussion: LOC of college students with visual impairments was similar to their sighted counterparts. The better adjusted the person was to his or her visual impairment and the less worsening the status of visual impairment was, the higher internal LOC he or she had. Implications for practitioners: Families and society can help individuals with visual impairments build their internal LOC, by teaching them how to adjust to their disability and providing them the conditions to increase their independence. At the same time, preparing them for entering university may also help them develop their sense of internal LOC.